Silencing Cardiac Troponin I-Interacting Kinase Reduces Lipopolysaccharide-Induced Sepsis-Induced Myocardial Dysfunction in Rat by Regulating Apoptosis-Related Proteins. (27th May 2021) - Yang, Dong; Jiang, Yanzhou; Qian, Haixia; Liu, Xiaomin; Mi, Liguo
Abstract : The aim of this study was to investigate the effect of cardiac troponin I-interacting kinase ( TNNI3K ) on sepsis-induced myocardial dysfunction (SIMD) and further explore the underlying molecular mechanisms. In this study, a lipopolysaccharide- (LPS-) induced myocardial injury model was used. qRT-PCR was performed to detect the mRNA expression of TNNI3K . Western blot was conducted to quantitatively detect the expression of TNNI3K and apoptosis-related proteins (Bcl-2, Bax, and caspase-3). ELISA was performed to detect the content of lactate dehydrogenase (LDH) and creatine kinase (CK). TUNEL assay was used to detect the apoptosis of H9C2 cells. In LPS-induced H9C2 cells, TNNI3K was up regulated. Besides, the CK activity, the content of LDH, and the apoptosis of H9C2 cells were significantly increased after treatment with LPS. Silencing TNNI3K decreased the LDH release activity and CK activity and inhibited apoptosis of H9C2 cell. Further research illustrated that si-TNNI3K promoted the protein expression of Bcl-2 and decreased the protein expression of Bax and cleaved caspase-3. The study concluded that TNNI3K was upregulated in LPS-induced H9C2 cells. Importantly, functional research findings indicated that silencing TNNI3K alleviated LPS-induced H9C2 cell injury by regulating apoptosis-related proteins.